Association between FAT1 mutation and overall survival in patients with human papillomavirus–negative head and neck squamous cell carcinoma. (15th February 2016) - Kim, Ki Tae; Kim, Bo‐Sung; Kim, Ju Han
Abstract: Background: The purpose of this study was to characterize the mutation profile of FAT atypical cadherin 1 ( FAT1 ) and determine the prognostic significance of FAT1 mutation for overall survival in patients with human papillomavirus (HPV)‐negative head and neck squamous cell carcinoma (HNSCC). Methods: Data were downloaded from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) data portals and used as discovery and validation sets. FAT1 mutational status was determined in 234 and 37 patients with HPV‐negative HNSCC, respectively, and overall survival analysis was performed. For comparison, HPV‐positive patients were also analyzed for overall survival. Results: Most of the identified nonsynonymous somatic FAT1 mutations were loss‐of‐function mutations. FAT1 mutation was significantly associated with better overall survival in HPV‐negative patients from both the TCGA cohort ( p = .026) and the ICGC cohort ( p = .047), but not in HPV‐positive patients. Conclusion: FAT1 mutational status is a strong independent prognostic factor in patients with HPV‐negative HNSCC. © 2016 The Authors Head & Neck Published by Wiley Periodicals, Inc. Head Neck 38 : E2021–E2029, 2016